Chmura w bibliotece jako lekarstwo na chmury nad biblioteką na przykładzie bibliotek pedagogicznych - Wachowicz, Monika (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
Using the cloud computing has become universal nowadays. It permeated into private and professional life. The article presents examples of the ways of using cloud computing on various types of devices by teacher-librarians. The author assumes that cloud computing can solve problems related to the implementation of statutory tasks of libraries in some situations. Services available in the cloud are investigated by informatologists and topics trainings are often organized, both by librarians and for librarians. According to the author, working in the cloud does not pose a threat to the identity of the pedagogical library, but it is only a new tool to support activities of such an institution. Farthermore, cloud computing should be assumed with the knowledge of its capabilities and limitations.